PROBLEMS OF THE RESEARCH OF EARLY URBAN PROCESSES IN THE KHOREZM OASIS (TAMADDUN NURI JURNALI, 2025)
This article discusses issues related to the study of urbanization processes in the ancient Khorezm region. The opinions and perspectives of researchers on how the process of urbanization unfolded in the Khorezm oasis during ancient times are examined.